Optimization strategies to eliminate interface conflicts in complex supply chains of construction projects - Ju, Qianqian; Ding, Lieyun; Skibniewski, Miroslaw J. (Journal of Civil Engineering and Management, 2017)
The supply chains of complex construction projects are characterized by multi-disciplinary participants, adversarial short-term relationships and fragmentations in project delivery procedures. Multi-disciplinary participants tend to make decisions on project activities based on their own objectives and value systems independently with little regard of holistic project performance. The lack of common values results in a limited understanding of how behaviors of one discipline impact on the related disciplines. This has led to tons of interface conflicts which ultimately affect project effectiveness. This paper investigates this problem by discussing Interface Value for the core players to understand the value-driven behaviors on the boundaries among owner and multiple prime contractors in complex construction projects. Two types of interface conflicts are recognized and defined. Value Optimization Strategy is proposed under status quo delivery methods by adjusting and reallocating interface responsibilities between related contractors. Improvements of procurement procedures are the key solutions to interface conflicts. Prospects of integrated project delivery (IPD) in eliminating interface conflicts are also discussed. The paper concludes that Value Optimization Strategy and IPD-based approach are expected to eliminate interface conflicts of complex construction projects, integrate the complex supply chain and lower the potential risks for project delivery delay and cost overrun.First published online: 03 Apr 2017